Worlds apart, learning together: A typology of international higher education students’ academic and social integration - Casas Trujillo, Jennyfer Paola; Dabney-Fekete, Ilona (Journal of International Students, 2026)
This qualitative research examined the academic and social integration of international students at a Central European university by conducting in-depth, semi-structured interviews in the 2023-2024 academic year. Via purposive sampling, thirty participants were selected, and a typology based on their integration experiences was developed through thematic analysis. Herein, we identified four distinct and well-defined student types: (1) focused scholars, prioritizing academics with scant social interaction; (2) engaged achievers, who maintain a balance between academic and social life; (3) overwhelmed isolates, who struggle in both areas, mainly due to cultural disconnectedness and stress; and (4) resilient networkers, who, despite several academic challenges, cope by leaning on their social connections. The results highlight the complex interplay among individual traits, cultural influences, academic demands and pressures, and institutional support in shaping integration outcomes.